1990
DOI: 10.1351/pac199062071325
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids and isoprenoids as defensive and signalling agents among insects

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This insect can now tolerate cardiac glycosides; however, adaptations are even more advanced, since Danaus can actively sequester cardenolides and store them in its integument as acquired defence compounds against predators. A similar strategy has been observed for the sequestration of cardiac glycosides in aphids, bugs and Lepidoptera, for PAs in beetles and Lepidoptera (for reviews, see Meinwald, 1990;Brown and Trigo, 1995;Hartmann and Witte, 1995) and for QAs in aphids and moths (Wink, 1992). In the case of some arctiid moth, the acquired PAs serve as a precursor for pheromones, which are dissipated from coremata that are only developed if the larvae feed on PAs (Schneider et al, 1982).…”
Section: Animal Responses: Detoxification Mechanisms and Adaptationsmentioning
confidence: 66%
See 1 more Smart Citation
“…This insect can now tolerate cardiac glycosides; however, adaptations are even more advanced, since Danaus can actively sequester cardenolides and store them in its integument as acquired defence compounds against predators. A similar strategy has been observed for the sequestration of cardiac glycosides in aphids, bugs and Lepidoptera, for PAs in beetles and Lepidoptera (for reviews, see Meinwald, 1990;Brown and Trigo, 1995;Hartmann and Witte, 1995) and for QAs in aphids and moths (Wink, 1992). In the case of some arctiid moth, the acquired PAs serve as a precursor for pheromones, which are dissipated from coremata that are only developed if the larvae feed on PAs (Schneider et al, 1982).…”
Section: Animal Responses: Detoxification Mechanisms and Adaptationsmentioning
confidence: 66%
“…Quite a number of insect herbivores but only few vertebrates have adapted to the defence chemistry of a given host plant in a particularly close way (for overviews, see Blum, 1981;Meinwald, 1990;Harborne, 1993;Bernays and Chapman, 1994;Brown and Trigo, 1995;Hartmann and Witte, 1995;Braekman et al, 1998;Roberts and Wink, 1998;Eisner et al, 2005). As a first step in adaptation, these organisms must develop an insensitivity or tolerance against the dietary toxin.…”
Section: Animal Responses: Detoxification Mechanisms and Adaptationsmentioning
confidence: 99%
“…This insect can now tolerate cardiac glycosides; however, adaptations are even more advanced, since Danaus can actively sequester cardenolides and store them in its integument as acquired defensive compounds against predators. A similar strategy has been observed for the sequestration of cardiac glycosides in aphids, bugs and Lepidoptera, for pyrrolizidine alkaloids in beetles and Lepidoptera (Meinwald, 1990;Hartmann and Witte, 1995) and for quinolizidine alkaloids in aphids and moths (Wink, 1992). In the case of some arctiid moths, the acquired pyrrolizidine alkaloids (PAs) serve as precursors for pheromones, which are dissipated from coremata that are only developed if the larvae feed on PAs (Schneider, 1992).…”
Section: Animal Responses: Detoxification Mechanismsmentioning
confidence: 56%
“…Owen (1971) reported that danaine butterflies use withered and damaged plants and floral nectar as sources of alkaloids. D. chrysippus uses the pyrrolizidine alkaloids to protect itself from its predators and synthesizes the courtship pheromone; maternal and parental contributions of alkaloids play an important role to protect the most vulnerable stage, the egg (Meinwald 1990). This butterfly species and also D. plexippus when equipped with these alkaloids have been experimentally proved to be unpalatable to their predators by Edgar et al (1976).…”
Section: Discussionmentioning
confidence: 99%